2018
DOI: 10.1186/s12967-018-1508-5
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells mediate the antitumor activity of frankincense and myrrh in hepatocellular carcinoma

Abstract: BackgroundTumor-promoting inflammation is an emerging hallmark of cancer, which participates in both cancer progression and immune escape. Hepatocellular carcinoma (HCC) is a typical inflammation-related cancer with an extremely poor prognosis. Frankincense and myrrh are anti-inflammation agents commonly used in clinic. The purpose of this study is to investigate whether extract of frankincense and myrrh (FM) downregulates inflammatory microenvironment of HCC and thereby restores antitumor immune responses.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Recently, Xu et al [75] have explored the role of pro-inflammatory response as another novel perspective in the malignant progression of tumors and the tumor immune escape. Under the inducement of frankincense and myrrh (FM), the effects of CD8 + NKG2D + T cells enriched from human peripheral blood were observed on hepatoma cell lines HCKM3 and Hepa 1-6.…”
Section: Ifn-gamma Secreted By Nk Cells Exerts Anti-hepatocarcinoma Amentioning
confidence: 99%
“…Recently, Xu et al [75] have explored the role of pro-inflammatory response as another novel perspective in the malignant progression of tumors and the tumor immune escape. Under the inducement of frankincense and myrrh (FM), the effects of CD8 + NKG2D + T cells enriched from human peripheral blood were observed on hepatoma cell lines HCKM3 and Hepa 1-6.…”
Section: Ifn-gamma Secreted By Nk Cells Exerts Anti-hepatocarcinoma Amentioning
confidence: 99%
“…It comprises numerous components that possess antioxidant and anti-inflammatory effects [9,10]. Likewise, myrrh oil has anticancer [11,12], analgesic [11,13] antibacterial [14], and antithrombin activities [15]. Recently, myrrh oil has been formulated as a nanoemulsion for enhancement of the antihyperlipidemic effect of atorvastatin [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our animal experiments verified the findings of in vitro experiments. Previous research confirmed that myrrh (or guggulsterone) has an anti-tumor effect on mice [17,41,42]. The tumor size was significantly smaller in myrrh-treated animals compared with that in the control group.…”
Section: Discussionmentioning
confidence: 77%